CHANGES IN BIOSAFETY PROTOCOLS IN THE TIME OF COVID AND THEIR EMOTIONAL IMPACT ON DENTISTRY GRADUATES - Gonçalves da Silva, Nicoli; Pereira Butze, Juliane (Health and Society, 2023)
Introduction: in March 2020, the World Health Organization declared Covid-19 a pandemic, due to its rapid spread. As the virus behaves in different ways and in some cases it can be fatal, many changes have occurred, including those related to biosecurity in hospitals and dental clinics. Aim: to evaluate the changes in biosafety protocols and the anxiety rates of undergraduate dentistry students. Methods: 100 academics who were enrolled in at least one discipline with clinical care for patients and which has a biosafety protocol were invited to participate in the research. The questions addressed were related to personal data (age, gender) and an adapted questionnaire on “Biosecurity in times of Covid” and a questionnaire on “Fear and Anxiety in the face of the coronavirus pandemic”. Results: A total of 100 academics from the University Center of Serra Gaúcha (FSG) participated in the research. Of these, 20 (20%) were male and 80 (80%) were female. The average age of participants was 22.8 years. Of these 100 students, 13 were in the 4th semester of the course, 39 were in the 6th semester, 23 were in the 8th and 25 in the 10th semester of the course. When asked if they felt fear when hearing that people were dying from COVID-19, 66% of academics said they felt fear. Regarding the fear of taking the infection from the clinic to the family, 91% of students said they were afraid. Next, students were asked if they were afraid of talking to patients in closed environments, only 12% said they were afraid. Sixty percent (60%) of students say they feel anxious when providing care to patients who have a cough or are suspected to be infected with the COVID-19 virus. Conclusion: negative effects on students’ mental health, such as fear and anxiety due to the risk of contamination and transmission of the COVID-19 virus, have been caused, requiring the implementation of mental health promotion strategies, especially if the pandemic extends.